Quantitative analysis of wavelength dependence of thermal perception - Akihisa Nomoto; Yoshiichi Ozeki; Miyoko Oiwake; Ryo Hisayama; Yutaro Ogawa; Mizuho Akimoto; Shin-ichi Tanabe (Elsevier, 2024)
In recent years, significant progress has been made in the development of materials that selectively reflect or absorb radiation in specific wavelength ranges. Previous studies have shown that the same intensity of radiation can produce different degrees of thermal perception depending on its wavelength. This difference is thought to be the optical properties of the skin. However, these findings have not been quantitatively verified yet. The purpose of this study is to quantitatively analyze the effects of radiation of different wavelength ranges on thermal sensation. We conducted a human subject experiment and discovered that far-infrared radiation causes a warmer and more uncomfortable sensation than near-infrared radiation. To interpret these results, we developed a new mathematical model that predicts thermal perception caused by radiation of different wavelengths. The model is based on a heat diffusion equation within the skin and considers the optical properties of the skin to simulate thermoreceptor activities in response to given spectral irradiances. Our model explained the observed phenomenon in our and previous experiments, where the same intensity of radiation but at different wavelengths can produce different degrees of thermal perception, in terms of physiological mechanisms. Additionally, the model revealed a hierarchy in thermal sensation, with far-infrared radiation being perceived as the warmest, followed by mid-infrared, visible, and near-infrared radiation. These findings are crucial for designing materials that selectively reflect or absorb radiation in specific wavelength ranges, and for developing heaters that provide efficient heating with low energy consumption.